2015
DOI: 10.1038/srep14810
|View full text |Cite|
|
Sign up to set email alerts
|

New reconstruction of the Wiwaxia scleritome, with data from Chengjiang juveniles

Abstract: Wiwaxiids are a problematic group of scale-covered lophotrochozoans known from Cambrian Stages 3–5. Their imbricating dorsal scleritome of leaf-like scales has prompted comparison with various annelids and molluscs, and has been used as a template to reconstruct the articulation pattern of isolated Small Shelly Fossils. The first articulated specimens of Wiwaxia from the Cambrian Stage 3 Chengjiang Konservat-Lagerstätte show that the Wiwaxia scleritome comprised nine equivalent transverse rows associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 49 publications
(67 reference statements)
0
27
0
Order By: Relevance
“…An equivalent sclerite arrangement was once envisaged in Wiwaxia 15,23 , but recent studies 8,9 have shown that the Wiwaxia scleritome conforms to a metameric architecture, comprising 8–9 transverse rows (Fig. 3c,g).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…An equivalent sclerite arrangement was once envisaged in Wiwaxia 15,23 , but recent studies 8,9 have shown that the Wiwaxia scleritome conforms to a metameric architecture, comprising 8–9 transverse rows (Fig. 3c,g).…”
Section: Discussionmentioning
confidence: 94%
“…If, on the other hand, brachiozoans evolved from a halkieriid-like ancestor, then multi-element scleritomes characterise the earliest brachiozoans as well as molluscs and annelids 9 (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations